Bilateral renal involvement in diffuse large B-cell lymphoma on fluorodeoxyglucose positron emission tomography/computed tomography - Benameur, Yassir; Hammani, Adnane; Doghmi, Kamal; Doudouh, Abderrahim (World Journal of Nuclear Medicine, 2021)
Secondary renal involvement in patients with diffuse large B-cell lymphoma (DLBCL) is rare and associated with poor prognosis. We, hereby, described a case of a patient diagnosed with DLBCL, in whom bilateral renal involvement was detected on 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). The patient received 4 courses of chemotherapy, and follow-up 18F-FDG PET/CT revealed the complete resolution of the diffuse increased renal 18F-FDG uptake. Renal lymphoma is uncommon and 18F-FDG PET/CT is particularly useful for detecting extranodal involvement in DLBLC.
Keywords: 18F-fluorodeoxyglucose positron emission tomography/computed tomography; diffuse large B-cell lymphoma; renal 18F-FDG uptake; renal lymphoma